Characterization of Asian clam, Corbicula fluminea, reproductive biology and larviculture in recirculating aquaculture system (RAS) - Mohd Zharif Ramli (2022)
Etak, Corbicula fluminea is an important edible freshwater bivalve in Asia. The population of C.fluminea is generally known as Asian clam. Its population was found to decline in the habitat which led to higher prices in the market. Hence, this research has been carried out to produce C.fluminea seeds in the hatchery. In this study, C.fluminea species were identified and characterised, emphasising on the phenotype and genotype. The broodstock was obtained from the natural habitat and reared in the hatchery. Then, the captive broodstocks’ reproductive biology, maturity, and gametogenesis were examined through histological analysis. The breeding induction incorporated thermal, salinity, and gonad suspension manipulation to induce the broodstocks to spawn. The larvae development from the marsupial until benthic stages were recorded. Finally, the released larvae in the breeding tanks were harvested and reared in a compact recirculating aquaculture system (RAS) for survival, growth, and development evaluation. Findings show that morphotypes and paratypes characterise the phenotype of seven C.fluminea populations based on their geography and demography. Unique morphometric characters such as shell height (SH), shell width (SW), umbo length (UL), anterior length (AL), and posterior length (PL) were found to be significantly different (p<0.05) existed in evaluated samples. The analysis of mtDNA COI, cytb, and rDNA18S had anchored the phenotypic analysis. The mtDNA COI exhibits the genotype of the C.fluminea, which certainly separates from the brackish population. Eleven haplotypes were determined using mtDNA COI and portrayed the inference of the C.fluminea lineages. Hence, this polymorphism indicates the population’s genetic diversity, where the result is priorly used for the selection of broodstocks. The broodstocks' condition index (CI) value was greater in the hatchery culture, which indicates better growth. The reproductive biology of this clam has proved that C.fluminea is a hermaphrodite organism. Besides, the gonad index (GI) has revealed the gonad development stages and the dominant gonads of the broodstocks. Photomicrographs reveal that the oocytes and spermatocytes follicles co-existed in evaluated samples. Besides, this analysis also demonstrated the gonadal development (rest/spent, gametogenesis, mature, spawning) of cultured hatchery clam. The CI value is parallel with the GI value, where the higher CI value corresponds to the mature stage. The mature broodstock was selected, and induction was made by integrating the temperature, salinity, and gamete suspensions. Compared with natural spawning, the recent procedure had produced a significant number (29,724.33±4784.88 larvae). Concurrently, the development of early life stages was monitored and as a result, three phases were determined; marsupial, planktotrophic and benthic stages were recorded. Finally, the growth and development of the larvae (planktotrophic) were evaluated and reared in a compact recirculating aquaculture system (RAS) which has been extended to the benthic stage (0-80 d) (size:1mm). Significant growth (p<0.05) was found in larvae reared in the rearing chamber supplemented with the substrate (fine sand) compared with non-substrate. In addition, the larvae growth in both treatments was recorded higher (p<0.05) at age 50-80 d. However, the survival rate was significantly lower in non-substrate (25%) compared with substrate (43%) rearing. Therefore, this study unprecedentedly discovered the potential of the C.fluminea to be reared and propagated in the hatchery and possibly cultivates as a new aquaculture species.